Gradbena pogodba s fiksno ceno in spremenjene okoliščine - Kranjc, Vesna (Podjetje in delo, 2022)
Recently, a range of products has become significantly more expensive, which makes it difficult to fulfill contracts concluded under different market conditions. This is particularly pronounced for construction contracts. A number of construction contracts include the fixed price clause. The paper clarifies whether the invariable or fixed price clause under Article 656 of the Obligations Code allows the contractor to request a price change if the current situation was unexpected. It also clarifies whether public procurement rules allow contracting authorities to adapt prices to changed circumstances.
Keywords: amendment of contract; cena je fiksna; changed circumstances; construction contract; fixed price; gradbena pogodba; hardship; javno naročilo gradnje; oteženost izpolnitve; public work contract; sprememba pogodbe; spremenjene okoliščine